Yusubov, Nizami - (:unkn) unknown (My University, 2026)
Nizami Yusubov Damir was born on February 2, 1965, in the city of Lankaran, in a family of civil servants. From 1972 to 1982, he received his secondary education at School No. 2 in Lankaran. Additionally, during the 1981-1982 academic year, as a 10th-grade student, he completed a two-year Correspondence Physics School at Lomonosov Moscow State University in one year. During his school years, he actively participated in the public life of the city and was a participant and winner of various academic Olympiads. In 1982, he entered the Azerbaijan Polytechnic Institute to study Mechanical Engineering Technology, Metal-Cutting Machines, and Tools. According to a decision made by the Soviet Union, after completing his first year, he served in the army from 1983 to 1985. After completing two years of military service, he resumed his studies at the Azerbaijan Polytechnic Institute from 1985 to 1989. During his university years, he was an excellent student and a recipient of the Lenin scholarship. In 1989, Nizami Yusubov Damir graduated with distinction from the Azerbaijan Polytechnic Institute, specializing in Mechanical Engineering Technology, Metal-Cutting Machines, and Tools. Based on the recommendation of the Department of Mechanical Engineering Technology and a decision by the Faculty's Scientific Council, he was retained as a trainee researcher in the department. In September 1990, N.D. Yusubov was sent to the target postgraduate program at Chelyabinsk Polytechnic Institute (later Chelyabinsk State Technical University, currently South Ural State University). On January 25, 1993, he defended his candidate's dissertation ahead of schedule on the topic "Optimization of Surface Processing Plans by Productivity Criteria on Turret Lathes" in the field of Mechanical Engineering Technology (specialty 05.02.08), earning the degree of Candidate of Technical Sciences. Since October 1993, Nizami Yusubov Damir has worked as an Assistant in the Department of Mechanical Engineering Technology, becoming a Senior Lecturer in November 1994 and an Associate Professor in November 1995. From November 2013 to September 9, 2015, he held the position of Professor. By the order of the Minister of Education of the Republic of Azerbaijan, Mikayil Jabbarov, dated September 9, 2015 (No. 11/944), Professor Nizami Yusubov Damir was appointed Vice-Rector for Academic Affairs at Lankaran State University (LSU). From March 29, 2016, to May 30, 2016, he temporarily assumed the role of Acting Rector of LSU. On February 2, 1998, by the decision of the Supreme Attestation Commission under the President of the Republic of Azerbaijan, N.D. Yusubov received the academic title of Associate Professor in the Department of Mechanical Engineering Technology. On December 2, 2009, he defended his doctoral dissertation on the topic "Improving the Efficiency of Multi-spindle Machining on Turret Lathe Groups" in the specialty of Mechanical Engineering Technology (05.02.08) at the Dissertation Council D. 02. 171 of Azerbaijan Technical University. On January 7, 2011, by the decision of the Supreme Attestation Commission under the President of the Republic of Azerbaijan, he was awarded the degree of Doctor of Technical Sciences. On May 22, 2015, N.D. Yusubov was awarded the academic title of Professor in the Department of Mechanical Engineering Technology by the same commission. He is the author of over 350 scientific and educational-methodical works, including 1 reference material (published in Russia), 1 guiding technical material, 5 inventions, 4 monographs (3 of which were published by AV Akademikerverlag Gmbh & Co. KG / LAP LAMBERT Academic Publishing in Saarbrücken, Germany), 3 textbooks, 10 teaching aids (one of which was published in Russia), 10 methodological guidelines, 1 methodological manual, and 75 subject programs. Of his scientific works, 58 have been published in leading technical journals and magazines in the USA, Germany, Sweden, Switzerland, France, Malaysia, Russia, Turkey, Belarus, Ukraine, and Kazakhstan. He has presented at various international and national scientific-technical and methodological conferences. One of his PhD students has successfully defended their dissertation in the field of technical sciences. Before being appointed as the Vice Rector for Academic Affairs at LSU, N.D. Yusubov lectured at the Mechanical Engineering Technology Department at AzTU, conducted laboratory and practical classes, and supervised course projects and graduation theses, as well as teaching and production internships. He served as the responsible executor of state-funded scientific and technical projects within the department and continues to lead scientific research initiatives. N.D.Yusubov completed a German language course at the Goethe Institute in Iserlohn, Germany, from August 4, 1996, to September 26, 1996. Through DAAD (German Academic Exchange Service), he conducted research at the Technical University of Braunschweig’s Institute of Machine Tools and Manufacturing Technology (for 1 year and 2 months from September 27, 1996, to November 15, 1997), at the Institute of Production Technology at the Technical University of Dresden (for 3 months from August 1, 2001, to October 31, 2001), and at the Chair of Machine Tools Laboratory at the Aachen University of Technology (for 2 months from August 1, 2012, to September 30, 2012). He participated in scientific exchanges and colloquia related to the German higher education system. On February 21, 2015, through March 15, 2015, Yusubov completed the International Visitor Leadership Program (IVLP) course on "Higher Education Management in the USA" organized by the U.S. Department of State and received an international certificate. N.D. Yusubov conducted scientific research as a visiting professor at the Institute of Production Technology at Dresden University of Technology from June 1, 2015, to July 31, 2015, where he also presented a report at a scientific colloquium. Furthermore, upon the invitation of DAAD, he worked at the Fraunhofer Institute for Large Structures in Production Technology and the Department of Production Technologies at the University of Rostock in Germany from July 1, 2023, to September 30, 2023, for the purpose of conducting research. N.D. Yusubov served as the deputy dean for scientific work of the Faculty of Mechanical Engineering from 1994 to 1996. He was a member of the scientific seminar of the D02.171 Dissertation Council at AzTU from 2006 to 2010 and 2011 to 2014. Additionally, from 2011 to 2014, he was a member of the D.02.171 Dissertation Council at AzTU, which awards academic degrees (Ph.D. and Doctor of Sciences). From February 3, 2020, to November 1, 2022, N.D. Yusubov was a member of the ED 2.32 Dissertation Council and served as the chair of the seminar for the specialization 3313.01 “Mechanical Engineering Technology”. N.D. Yusubov served as a member of the Scientific Council of Lankaran State University (LSU) from September 14, 2015, to November 1, 2016, and was the chairman of the Scientific and Methodological Council of LSU from November 2, 2015, to November 1, 2016. In 2024, he was among the winners of the “Main Grant Competition-2024” organized by the Azerbaijan Science Fund, dedicated to the “Year of Solidarity for the Green World” (AEF-MGC-2024-2(50)). Since April 1, 2014, he has been a member of the editorial board of the journal "Vestnik YuUrGU" in the " Mechanical Engineering" series at South Ural State University in Chelyabinsk, Russia. From April 17, 2015, until the end of 2016, he was also a member of the Expert Council of the Technical Sciences Department of the Higher Attestation Commission under the President of the Republic of Azerbaijan. Currently, he is a member of the editorial boards of the journals MACHINE SCIENCE and CIFRA. МАШИНОСТРОЕНИЕ. N.D. Yusubov was awarded the honorary title of "Honored Engineer" by the decree of the President of the Republic of Azerbaijan dated December 30, 2020, No. 2394. N.D. Yusubov worked actively in the public affairs of the university, faculty, and department during his time at AzTU.